Calcification of the intracranial carotid artery and its relation to the clinical and angiographic picture: an angiographic classification of asteriosclerosis cerebri - Valter Seixas (Arquivos de Neuro-Psiquiatria)
Fifty six patients with arteriosclerosis cerebri confirmed by X-rays examinations were clinically and angiographically studied. Calcifications of the carotid artery were found predominantly in human beings between the ages of 55 and 65 and more often among men than among women, the proportion being 2.5 to 1. Nearly all arteriosclerotic patients with calcium deposits in the carotid artery showed several neurological and mental deficits, the most frequent initial symptoms being motor disturbances. Angiographic anormalities found in these patients can be classed into 3 groups: (a) grade I— wavy course of the cerebral vessels, small number of peripheral brain vessels, formation of small knots, prolonged circulation time, arteria cerebri anterior with angular form, straight course and broad caliber; (b) grade II— partial block, irregularities of wall and caliber, aneurysmal formations; (c) grade III— total block of some vessels of the carotid system preventing a generalized or localized cerebral blood supply. Grades II and III angiographic abnormalities were most often seen at the syphon and at the carotid bifurcation in the neck (site of predilection). Most patients with a progressive clinical course belonged to the I group. The course of the disease did not differ in patients with grades II and III angiographic changes since usually the illness had an apoplectiform onset. Arteriosclerotic degenerative irregularities within the layers of the arteries (up to atheromatous patches) may occur without reducing the arterial lumen. In such cases the patients may remain asymptomatic until there is a decompensation in the brain circulation due to many causes. Foram estudados, clínica e angiogràficamente, 56 pacientes com arte-riosclerose cerebral comprovada mediante visibilização radiológica de calcificações localizadas na porção intracraniana da artéria carótida interna. Calcificações da artéria carótida interna ocorrem com mais freqüência em indivíduos com idade entre 55 e 65 anos. Os homens são mais afetados do que as mulheres na proporção de 2,5:1. Os sintomas iniciam-se preferentemente com distúrbios motores. Posteriormente foram verificados, ao mesmo tempo e no mesmo paciente, vários distúrbios neurológicos e psíquicos. Nesses pacientes as alterações angiográficas do sistema carotídeo podem ser classificadas em 3 grupos: a) 1.° grau— percurso ondulado das artérias cerebrais, pobreza vascular na periferia, formação de acotovelamentos das artérias, aumento do tempo de circulação, artéria cerebral anterior com forma angulada; b) 2.° grau— oclusões parciais, irregularidades das paredes e do calibre das artérias e formações aneurismáticas; c) 3.° grau— oclusões totais de artérias do sistema carotídeo. As alterações de 2.° e 3.° grau foram observadas com maior freqüência nas proximidades do sifão carotídeo e junto à origem da carótida interna (zonas de predileção). Na maioria dos casos cuja sintomatologia evoluiu lenta e progressivamente foram encontradas alterações de 1.° grau. Entre os dois grupos de pacientes com oclusões parciais ou totais (2.° e 3.° grau) não foi verificada qualquer diferença na evolução clínica pois na maioria dos casos destes dois grupos, a sintomatologia começou de maneira abrupta. Podem ser encontradas degenerações arterioscleróticas (até placas ateromatosas) nas paredes arteriais, sem que ocorra diminuição da luz do vaso. Os doentes podem permanecer assintomáticos até que, por uma causa eventual, a circulação cerebral se descompense.